IDENTIFIKASI PROSES PEMBENTUKAN PAPER CUP PADA MESIN FORMING ZBJ-X12 DAN KAJIAN PERMASALAHANNYA - Imam Hari Prastio; Septia Ardiani; Alfred Satyahadi (Politeknik Negeri Media Kreatif, 2022)
Paper cups are disposable cups made of paper-based material covered with laminated plastic to prevent leakage. Paper Cups have two types, namely the hot cup and cold cup. The hot cup type paper cup is a paper cup that is specifically for hot drinks that has a onesided PE laminated layer. In producing paper cup packaging, one of the machines used is the ZBJ-X12 paper cup forming machine which has high technology in producing paper cups. This machine uses ultrasonic welding to glue the body of the paper cup and uses a heater to glue the bottom of the paper cup, the gluing process on this machine does not use glue as an additional material. In this machine, problems are often encountered while carrying out the production process, so that the production process becomes hampered and affects the quality of a product. Problems that often occur include tearing at the lip of the cup, paper cup stuck in the heater, and the bottom cup not sticking together perfectly. This problem is often encountered and hampers the production process and affects the quality of the product being produced. Based on the results of data collection in the form of observations, interviews, and literature studies, it can be concluded that machine maintenance and the knowledge and skills of operators on machines can affect the smooth production process and the quality of a product being produced.